2007
DOI: 10.1016/j.jsat.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C management by addiction medicine physicians: Results from a national survey

Abstract: Drug users are disproportionately affected by hepatitis C virus (HCV), yet they face barriers to health care that place them at risk for levels of HCV-related care that are lower than those of nondrug users. Substance abuse treatment physicians may treat more HCV-infected persons than other generalist physicians, yet little is known about how such physicians facilitate HCV-related care. We conducted a nationwide survey of American Society of Addiction Medicine physicians (n = 320) to determine substance abuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…Finally, providers are often reluctant to provide HCV treatment to active injecting drug users 66,67. One of the clinician-related barriers to treating PWID is fear of relapse into drug injecting and consequent HCV reinfection after successful HCV treatment.…”
Section: Treatment Uptake and Barriersmentioning
confidence: 99%
“…Finally, providers are often reluctant to provide HCV treatment to active injecting drug users 66,67. One of the clinician-related barriers to treating PWID is fear of relapse into drug injecting and consequent HCV reinfection after successful HCV treatment.…”
Section: Treatment Uptake and Barriersmentioning
confidence: 99%
“…Litwin et al found that, although only 1% of primary care physicians were treating CHC, 13% were willing to do so with appropriate training. 21 Novel ways of training primary care staff are emerging. Through Project ECHO (Extension for Community Healthcare Outcomes), the University of New Mexico in the US evaluated a teleconferencing approach whereby primary care clinicians meet weekly with specialists via teleconference.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…However concerns have been raised about the quality of management as one study indicated that patients treated in specialized centres in Switzerland were more likely to receive screening for HCV compared to GP's 13 which contrasts results from USA, Australia and the United Kingdom [14][15][16] . We hypothesized that in Switzerland a GP with a high level of commitment but without a special intervention can achieve CHC assessment rates comparable to specialized centres in opioid addicts (with and without a history of IDU) .…”
Section: Introductionmentioning
confidence: 99%